The Influence of Country of Origin and Academic Level on Asian Students’ Gains of Learning - Bista, Krishna (Journal of International Students, 2018)
The author examines whether gains of learning of Asian students are the same or different if they are from (a) East Asia, (b) South and Central Asia, or (c) Southeast Asia at undergraduate and graduate levels. Results indicated that East Asian students’ gains of learning in personal development, science and development, general education, vocational preparation, and intellectual skills were statistically different from other students from South and Central Asia and Southeast Asia. Graduate Asian students’ gains of learning in all domains were found higher than undergraduate Asian students’ gains of learning. Based on these findings, the author offers implications and recommendations for educators and practitioners to improve international students’ support and their college learning experiences.